Perancangan Interior Museum Basket Indonesia di Surabaya - Chatarina Regina Soebekti (Intra, 2017)
Basketball is a sport whose development has increased enough at this time in Indonesia. Increasing number of newly formed basketball club, many basketball school, and more people who create new business by building a basketball court, sells equipment, accessories for the needs of basketball. Surabaya is one of the cities that took part in developing basketball in Indonesia, PT. DBL is a company under the auspices of the Jawa Pos Group who took part in developing this sport. The problems that exist at the moment is there is no Indonesian basketball museum at this time, behind the development of basketball at this time, need to record the origin and basketball journey in Indonesia.Therefore it is necessary to be given a container that records it all with the existence of an Indonesian basketball museum. The current problem is the absence of Indonesian basketball museum in Surabaya. So it needs to be solved by creating the design of Indonesian Basketball Museum in Surabaya by using the concept of